Famílias e o cuidado em saúde mental a partir do centro de atenção psicossocial – CAPS - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This Course Conclusion Paper, at undergraduate level in the Social Work course, aims to present a theoretical-practical reflection on the theme of "Families and Mental Health Care", based on the experience of a compulsory curricular internship at the Psychosocial Care Centre (CAPS). It is the result of a literature review, as well as a report on the internship experience. It is important to note that the theme of the study focuses on theoretical categories such as families and mental health from the perspective of care, in order to give visibility to the expressions of the social question. The main aspects observed during the study show that the Psychosocial Care Centre (CAPS) in the city of Itaqui-RS has a significant demand in terms of users' families not participating in the groups on offer. Finally, through the internship experience it was possible to identify that the challenges at the CAPS are continuous in relation to users' family ties, given their importance in qualifying and enhancing the psychosocial rehabilitation of CAPS users. Thus, based on the information obtained in the internship field, a reflection was made on care, showing that the actions and family groups carried out are inseparable in the psychosocial rehabilitation of CAPS users.
Keywords: Famílias - Saúde mental; Política de saúde mental; Serviço Social; Families - Mental Health; Mental health policy; CNPQ::CIENCIAS SOCIAIS APLICADAS